2016
DOI: 10.11604/pamj.2016.23.57.7965
|View full text |Cite
|
Sign up to set email alerts
|

Intertrochanteric fracture non-unions with implant failure of the gamma nail

Abstract: Failure of internal fixation of intertrochanteric fracture is associated with delayed union or malunion resulting in persistent pain and diminished function. We report a rare case of implant failure of the gamma nail with intertrochanteric fracture non union treated by DCS plate screw and bone graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Strict monitoring is required to prevent implant loosening or breakage, which usually occurs at the level of the cervical screw regarded as a zone of weakness. 27 In our series we observed 02(0.5%) cases of pseudarthrosis including a case complicated with implant breakage. In recent literature, multicenter studies have reported incidence of Gamma implant failure from 0% to 0.4%.…”
Section: Discussionmentioning
confidence: 57%
“…Strict monitoring is required to prevent implant loosening or breakage, which usually occurs at the level of the cervical screw regarded as a zone of weakness. 27 In our series we observed 02(0.5%) cases of pseudarthrosis including a case complicated with implant breakage. In recent literature, multicenter studies have reported incidence of Gamma implant failure from 0% to 0.4%.…”
Section: Discussionmentioning
confidence: 57%
“…Most trochanteric fractures of the femur occur in elderly patients and require adequate treatment as soon as possible. Proximal femoral intramedullary nails—particularly PFNA and Gamma 3—are the most common choice during surgical treatment, however complications (e.g., cut through and cut-out) have been reported 1 2 3) . Therefore, gamma 3 nails with a U-blade lag screw are used for unstable fractures and high risk patients, but there are no comprehensive studies reporting postoperative outcomes 4) .…”
Section: Discussionmentioning
confidence: 99%
“…Trochanteric fractures can fail because of inappropriate axial load of body weight, the relative strengths of hip flexors and external rotators or displacement of fracture fragments. Fixation failure (e.g., metal breakage and nonunion after surgery) are most commonly the result of varus fixation, excessive weight bearing, and stress fracture caused by poor nutrition during recovery 1 7 8 9) . Gamma-3 nails are known to have a postoperative fracture rate of 2.0% to 5.7%, in part because of their structural design and material durability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations